Applying the principles of Good Governance in the Efforts of Guiding Out-of-School Children at Social Service Offices Takalar Regency - Ayu, Asri; Niswaty, Risma; Darwis, Muh.; Arhas, Sitti Hardiyanti (Universitas Negeri Makassar, 2019)
This study aims to determine efforts to foster school dropouts at the Takalar District Social Service Office. This type of research is a descriptive study with a qualitative approach. Indicators used as benchmarks in this study are accountability, transparency, participation, and the rule of law of the bureaucratic apparatus. Data collection techniques are done through observation, interviews, and documentation. The data analysis technique used consists of data reduction, data presentation, and drawing conclusions. The results of the research on the application of the principles of Good Governance in the effort of developing school dropouts at the Takalar District Social Service Office show that governance at the Social Service Office is good enough